Anaesthetic Management of a Neonate with Ebstein’s Anomaly Undergoing a Meningomyelocele Surgery: A Case Report - Prakriti; Monika Yadav; Vaishali Gupta; Komal Yadav; Shikha Garg (Journal of Clinical and Diagnostic Research)
Ebstein’s Anomaly (EA) is a congenital heart defect characterised by the downward displacement of the posterior and septal leaflets of the tricuspid valve toward the right ventricular apex. Hereby the authors discuss a 16-day-old female neonate with EA who underwent surgery for a ruptured meningocele. The baby, born at full term, had an Appearance, Pulse, Grimace, Activity and Respiration (APGAR) score of 7 at one minute and 9 at five minutes. Upon further observation, she showed multiple episodes of breath-holding and cyanosis. On examination, an enlarged head and swelling on the lumbar spine led to an ultrasound that confirmed hydrocephalus and meningocele. An Electrocardiogram (ECG) showed supraventricular tachycardia, and a chest X-ray revealed cardiomegaly. The diagnosis of EA was confirmed by two-dimensional (2D) echocardiography. General anaesthesia with inhalational induction was planned. Perioperative considerations for this patient included right-to-left shunting with the possibility of paradoxical emboli, prolonged onset time for intravenous drugs due to pooling and recirculation of blood in the right atrium, increased Pulmonary Vascular Resistance (PVR), perioperative pulmonary hypertension, right and left ventricular dysfunction, and arrhythmias. Key cardiovascular goals for this patient included maintaining normal sinus rhythm, ensuring adequate preload while avoiding significant changes in Systemic Vascular Resistance (SVR) or PVR, avoiding medications and factors that depress myocardial function, and promptly identifying haemodynamic instability or inadequate tissue perfusion with appropriate corrections. The surgery for excision and repair of the meningocele was uneventful, and the neonate was sent to the Neonatal Intensive Care Unit (NICU) for further monitoring.